O lugar fora do lugar: topografias sonoras do cinema documentário - Frederico Augusto Vianna de Assis Pessoa (2011)
This dissertation addresses the use of sound in non-fiction films through the analysis of four documentary films: Entuziazm or Simfonija Donbassa (1931) by Dziga Vertov, Titicut Follies (1967), by Frederick Wiseman, Chulas Fronteras (1974) by Les Blank and The Invisible Frame (2009) by Cynthia Beatt. First we talk about the four elements that constitute the sound track of a movie, which are voice, music, noises and silence and discuss those using Michel Chion and Johnny Wingstedt theories. After that we examine the definition and the field of non-fiction films, the six forms of documentary classified by Bill Nichols as well asthe articulation of sound and image within those forms. Afterwards we consider Fernão Pessoa Ramos arguments about ethics and politics of non-fiction films discussing the relations between aesthetic choices, mostly when sound is concerned and their political consequences.Finally, we apply the discussed concepts to the analysis of the four selected movies and try to delineate their sound and political topography.